GERAK PEMBERDAYAAN PEREMPUAN PEGIAT UMKM MELALUI PROSES REFLEKSI DIRI DI GEDANGSEWU, PARE, KEDIRI - Silviana, Ika (P3M IAIN KEDIRI, 2019)
The basic problem of development is equity to the smallest lines. This homework is not only the responsibility of the village government, but is an obligation for all people. Efforts to increase development need a continuous awareness building, covering various aspects and all parties. For rural people who still have many limitations, a simpler pattern is needed in creating a movement of empowerment. To facilitate development access for the community. Through the process of self-reflection which includes the stages of sensory knowledge, the stage of reasoning, and the stage of the ratio of Gedangsewu UMKM activists can begin to build awareness. All the step are the basis for managing the movement of empowerment based on development morality. With awareness-based activities, activists are able to interpret collective challenges, in order to create common purpose, by strengthening collective solidarity and identity, in order to preserve political resistance from a lifestyle that clings to a system that is rolling. Then efforts need to create independence from the mind to the step of empowerment.